SYNERGY OF BUMDES AND VILLAGE COOPERATIVES IN THE FREE NUTRITIOUS MEAL PROGRAM: RECONSTRUCTION OF LOCAL GOVERNMENT AUTHORITY BASED ON ECONOMIC DEMOCRACY AND WELFARE STATE - Dwijaya, Ananda Gymnastiar; Harmono, Harmono (Hukum Responsif, 2026)
The Free Nutritious Meal (MBG) program, as a national welfare policy, requires a food procurement system that not only ensures the availability of food for consumption but also encourages sustainable community economic development. However, in practice, the public food procurement structure has not been fully integrated with village economic institutions, so the potential for local production has not been fully utilized within the state welfare distribution system. This study aims to analyze the constitutional basis of local government authority in village economic integration, formulate a policy model for local commodity-based food procurement through the synergy of Village-Owned Enterprises and village cooperatives, and examine the implications of these policies on economic democracy and the welfare state. The research employs normative juridical methods with a comparative approach to laws, regulations, concepts, and policies. The results of the study show that local governments have constitutional legitimacy to integrate the village economy into public food supply programs through their authority over local economic development, community empowerment, and food security management. The local commodity-based food procurement policy model establishes a structural relationship between state demand and village communities' production capacity through the institutional synergy of BUMDes and cooperatives. This integration not only increases the effectiveness of food distribution but also reconstructs the welfare state's function from a redistribution mechanism to one of facilitating community-based social production, and strengthens the practice of economic democracy within Indonesia's constitutional system.